Ag- and B-TiO2 nanostructures: Preparation, characterization and their antileishmanial activity. (September 2017) - Noberi, Cansu; Kaya, Cengiz
Graphical abstract: Pure TiO2, Ag- containing TiO2 and B- containing TiO2 nanoparticles and nanotubes were synthesized using hydrothermal and sol–gel procedures as shown in the figure. As a boron precursor, very reactive amorphous B was used instead of boron oxide which is typically the most preferred in literature. All nanoparticles and nanotubes were investigated using a number of characterization methods. SEM and TEM analyses were helpful in order to understand the nanostructures in detail, whereas XRD was used to determine all of the phases present. An antimicrobial efficiency of the nanostructures MTT test was carried out against leishmanias. It was proven that doping both TiO2 nanoparticles and nanotubes with Ag and B-, increase their antileishmanial effect. Abstract: Silver (Ag) and boron (B) doped titanium dioxide (TiO2 ) nanoparticles and nanotubes were synthesized using a combination of hydrothermal and sol gel techniques. In order to synthesize B-TiO2, very reactive nano amorphous boron was used as a boron source instead of boron oxide. It is shown that doping with both Ag and B enhances antileishmanial activity of TiO2 nanoparticles and nanotubes. It is also found that doping TiO2 with nonmetallic elements suppresses the grain growth of titania. Detailed TEM observations were conducted to analyze nanotube structures. All the phases were determined using XRD analyses.